(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This research investigates the mediating impact of green brand image (GBI), green WOM (GWOM), and green satisfaction (GS) on green brand equity (GBE). It also examines the effect of greenwash (GW) on GBE. The focus of this research is Jordanian customers who have made green product purchases. Based on the findings, greenwash (GW) has a detrimental impact on GBE. Moreover, this research found that GW has a negative relationship with GBI, GS and, GWOM. Additionally, GS is strongly positively impacted by GBI. Further, GWOM benefits from GS. Furthermore, green brandequity is significantly impacted by GBI, GS, and GWOM. Moreover, this research confirms that the negative association between GW and green brandequity is partially mediated by GBI, GS, and GWOM. To promote GBE, this research recommends companies reduce their GW practices while increasing their customers’ GS, GBI, and GWOM.